Analisis Pasar Wisata Nusantara di Taman Nasional Gunung Merapi Pasca terjadinya Erupsi - Nikasius Jonet Sinangjoyo (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2012)
This study is aimed to give input for developing tourism at Merapi Mount National Park (TNGM) after the eruption of volcano Merapi, it has goals such as: to analysis domestic and to make a marketing development strategy of this area. a collected by using questionnaire methods, interview and field observation. The sampling method was accidental sampling, with an amount of about 100 respondents. The data include tourist and visiting characteristics, tourist perception. Implementation could be performed by using a marketing mix, which is a product, price, place and promotion. The product policy should be conducted by increasing product quality. Furthermore, the pricing policy could use modified flexible pricing. The distribution policy is recommended to utilize distribution channels like the community has a preference towards eco-culture and cooperation with all the components of tourism. Finally, the promotion policy should be performed by words of mouth promotions and information reported by the press.